Concentration analysis of hypoxi-inducible factor-1Î±; and vascular endothelial growth factor in patients with aortic aneurysm at different stages and its clinical significance - Xu, M; Zhang, Y; Tang, L; Huang, H (Cellular and Molecular Biology, 2016)
This study aims to investigate serum concentration of hypoxia inducible factor-1Î±; (HIF-1Î±) and vascular endothelial growth factor (VEGF) in patients with aneurysms at different stages, and to determine critical role in early diagnosis and evaluation of severity. A cohort of 102 cases of patients diagnosed as aneurysms during May 2012 to April 2015 in our hospital were retrospectively analyzed. Patients were divided into early stage group (n=32), mid-term group (n=34), and late stage group (n=36) according to severity of aneurysms. The measurement of concentration of HIF-1Î± and VEGF was detected by Enzyme”linked immunosorbent assays (ELISA). Serum level of HIF-1Î±; and VEGF was compared among different groups. The results showed that serum concentrations of HIF-1Î± (t=25.53, P<0.05) and VEGF (t=12.10, P<0.05) in early stage group were significantly higher than those in normal group. Serum concentrations of HIF-1Î± (t=25.63, P<0.05) and VEGF (t=9.71, P<0.05) in the mid-term group were significantly higher than those in the early stage group. Serum concentrations of HIF-1Î± (t=14.61, P<0.05) and VEGF (t=21.42, P<0.05) in the late stage group were significantly higher than those in the mid-term group. In conclusion, serum HIF-1Î± and VEGF has clinical value of early diagnosis and assessment of disease severity.